2014
DOI: 10.1111/cen.12470
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous pulsatile glucocorticoid replacement therapy

Abstract: SummaryThe glucocorticoid hormone cortisol is released in pulses resulting in a complex and dynamic ultradian rhythm of plasma cortisol that underlies the classical circadian rhythm. These oscillating levels are also seen at the level of tissues such as the brain and trigger pulses of gene activation and downstream signalling. Different patterns of glucocorticoid presentation (constant vs pulsatile) result not only in different patterns of gene regulation but also in different neuroendocrine and behavioural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
(55 reference statements)
1
29
0
1
Order By: Relevance
“…In health [6], major surgery [7] and critical illness [8], adrenocorticotropic hormone (ACTH) and cortisol are secreted in a pulsatile manner generated by the positive feedforward and negative feedback of these two hormones. This pulsatility is critical for patients with absolute cortisol deficiency [37, 38] to maintain normal glucocorticoid receptor (GR) signalling and optimal physiological function. The pulsatile secretion pattern also translates into the pattern of receptor binding [39], with continuous and intermittent binding yielding both quantitative and qualitative differences in gene transcription [40].…”
Section: Discussionmentioning
confidence: 99%
“…In health [6], major surgery [7] and critical illness [8], adrenocorticotropic hormone (ACTH) and cortisol are secreted in a pulsatile manner generated by the positive feedforward and negative feedback of these two hormones. This pulsatility is critical for patients with absolute cortisol deficiency [37, 38] to maintain normal glucocorticoid receptor (GR) signalling and optimal physiological function. The pulsatile secretion pattern also translates into the pattern of receptor binding [39], with continuous and intermittent binding yielding both quantitative and qualitative differences in gene transcription [40].…”
Section: Discussionmentioning
confidence: 99%
“…This preparation combines an outer coating layer that provides an immediate release of the drug and an extendedrelease HC core (Nilsson et al, 2014). Refining this paradigm, a pulsatile subcutaneous HC infusion pump has been validated to more closely mimic ultradian and circadian cortisol secretory pulsatility and showed that at comparable overall GC exposure, the pulsatile versus smooth pattern of cortisol secretion shapes a particular gene transcription pattern and subsequently specific neuroendocrine responses (Russell et al, 2014). This improved approximation of the physiological circadian cortisol rhythm translated into improved quality of life, reduced body weight, decreased blood pressure, and improved glucose metabolism in a study involving 64 patients with primary adrenal insufficiency (Johannsson et al, 2012).…”
Section: Gc Chronotherapymentioning
confidence: 99%
“…This provides us with a much easier opportunity to use pumps to replicate physiological pulses, as demonstrated by Russell and colleagues. 40 It is not yet clear to what extent it is important to replicate these rhythms to provide optimal treatment for patients with adrenal failure. Although we know that stress increases the size of ultradian pulses, 41,42 there have been no long-term studies on the modulation of ultradian rhythmicity in normal daily living.…”
Section: Subcutaneous Glucocorticoid Infusionsmentioning
confidence: 99%
“…Since the frequency of ultradian pulses simply depends on fixed delays in the feedforward‐feedback relationship between the pituitary corticotropes and the adrenal fasciculata cells, the circadian change in cortisol is determined by changes in pulse amplitude rather than pulse frequency. This provides us with a much easier opportunity to use pumps to replicate physiological pulses, as demonstrated by Russell and colleagues …”
Section: Introductionmentioning
confidence: 99%